‘Groaning wicked like a maddening dog’: Bestiality, Modernity and Irishness in J. M. Synge’s The Playboy of the Western World - Hélène Lecossois (Sillages Critiques)
In J. M. Synge’s The Playboy of the Western World, anxieties brought about by Ireland’s colonial modernity are given an especially powerful expression through an extensive recourse to animal imageries. This article proposes to read these imageries as indexes of (pre-) modernity, and as markers of the divide between rural and urban areas that modernity accentuated. It argues that the animal-like behaviour that Synge’s play calls for may be considered as a form of resistance to a hegemonic and early twentieth century conception of modernity. Alongside the trained, performing, modern Irish body that emerged in the theatre of the early 1900s there survived vestiges of a radically different form of embodiment associated with, for example, rural performance traditions such as faction fighting or keening. It was these other expressions of corporeality - less easily legible and more beastly - which piqued Synge’s interest and which, in Playboy, offer traces of an inexpungible and co-existing alternative to the modernity of the (Abbey) theatre as an institution.